2019
DOI: 10.1038/s41467-019-09988-z
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of cost effective battery storage

Abstract: Energy storage will be key to overcoming the intermittency and variability of renewable energy sources. Here, we propose a metric for the cost of energy storage and for identifying optimally sized storage systems. The levelized cost of energy storage is the minimum price per kWh that a potential investor requires in order to break even over the entire lifetime of the storage facility. We forecast the dynamics of this cost metric in the context of lithium-ion batteries and demonstrate its usefulness in identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(81 citation statements)
references
References 31 publications
0
67
0
Order By: Relevance
“…Energy storage [404][405][406] is an important issue for which different strategies and technologies exist. Among these, the development of batteries [407,408] certainly represents one of the major research tracks. However, hydrogen production from renewable electricity [409,410] and its storage [411] or pumping into power-togas networks [412,413] also plays an important future role.…”
Section: Liquefaction Of Fuels By the Magnetocaloric Effectmentioning
confidence: 99%
“…Energy storage [404][405][406] is an important issue for which different strategies and technologies exist. Among these, the development of batteries [407,408] certainly represents one of the major research tracks. However, hydrogen production from renewable electricity [409,410] and its storage [411] or pumping into power-togas networks [412,413] also plays an important future role.…”
Section: Liquefaction Of Fuels By the Magnetocaloric Effectmentioning
confidence: 99%
“…Regarding the parameters of the VRFB model previously described in (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), specifically the parameters U a ch − U h ch , U j ch − U n ch , U p ch , U q ch for charging and U a dis − U h dis , U j dis − U m dis for discharging; they can be found in [35][36][37]. Similarly, the parameters P a C and P b C related to the power converter efficiency have been obtained from the experimental data published in [38].…”
Section: Bess and Power Converter Modelsmentioning
confidence: 99%
“…However, when very low GHG emissions are required, BESS can be a critical device to achieve such an ambitious goal.In the case of energy provision for an isolated hybrid energy system (HES), incorporation of BESS becomes profitable due to the fact that the fuel consumption and operating hours of a conventional generator are considerably reduced. In the case of a grid-connected HES, retailing rates and feed-in tariffs as well as favorable resources are crucial for their successful adoption [6].Heuristic techniques are commonly used to carry out the optimal sizing of a specific HES. Consequently, some of them have been implemented in computational programs such as HOMER Pro ® [7], iHOGA ® [8], and Hybrid2 ® [9], among others.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further analyses have shown that renewable energy and storage systems can be used to fit useful load shapes at reasonable costs 16 as well as minimize behind the meter costs when differences in rates and feed-in tariffs allow for load shifting and demand response 17 . There also exists the potential for transmission and distribution infrastructure expansion deferral with the appropriate placement of energy storage systems within a network 18 .…”
Section: Introductionmentioning
confidence: 99%